France : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper analyzes the recent French inflation behavior. The paper demonstrates that the recent change in French headline inflation behavior resulted from a few idiosyncratic, id est, transient, factors. The paper describes the model setup and calibration of some crucial economic relations and parameters. The level of competition in labor and product markets in France and the other EU countries is discussed, including the size of markups. The paper also looks into the economic impact of increasing competition in each market separately and the advantages of coordinating reforms within the euro area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet